2020
DOI: 10.7600/jspfsm.69.307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature for cooling leg on intermittent exercise performance during half-time in a hot environment

Abstract: Intermittent exercise performance in a hot environment is lower than in temperate conditions. Cooling strategies at rest are important; however, the appropriate cooling temperature is not clear. The purpose of this study was to investigate the effect of temperature for cooling leg during half-time (HT) on intermittent exercise performance. Eleven men performed two pre-tests and three experimental trials of a 2 × 30 min intermittent exercise protocol in the heat (33°C; 50% relative humidity). During HT, three e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Castle et al [ 34 ] demonstrated that thigh cooling with an ice pack reduced Tm measured with a needle probe by approximately 3.5°C from 36.5 to 33°C, in turn improving subsequent intermittent exercise performance. In addition, Hasegawa et al [ 35 ] recently reported that a 12°C-ice pack decreased the Tm by approximately 3°C and attenuated the impairment to subsequent power output during intermittent sprint performance, albeit no improvement was observed using a 0°C-ice pack. Thus, combined cooling using both ice slurry ingestion and moderate cooling of the muscles may be an effective strategy during heat exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Castle et al [ 34 ] demonstrated that thigh cooling with an ice pack reduced Tm measured with a needle probe by approximately 3.5°C from 36.5 to 33°C, in turn improving subsequent intermittent exercise performance. In addition, Hasegawa et al [ 35 ] recently reported that a 12°C-ice pack decreased the Tm by approximately 3°C and attenuated the impairment to subsequent power output during intermittent sprint performance, albeit no improvement was observed using a 0°C-ice pack. Thus, combined cooling using both ice slurry ingestion and moderate cooling of the muscles may be an effective strategy during heat exposure.…”
Section: Discussionmentioning
confidence: 99%